Progress in the clinical application of constraint-induced therapy following stroke since 2014 - Cui, Yinxing; Ma, Ningyi; Liu, Xuncan; Lian, Yawen; Li, Yinghua; Xu, Guoxing; Zhang, Jiaming; Li, Zhenlan (Frontiers in Neurology, 2023)
Stroke is a group of cerebrovascular diseases with high prevalence and mortality rate. Stroke can induce many impairments, including motor and cognitive dysfunction, aphasia/dysarthria, dysphagia, and mood disorders, which may reduce the quality of life among the patients. Constraint-induced therapy has been proven to be an effective treatment method for stroke rehabilitation. It has been widely used in the recovery of limb motor dysfunction, aphasia, and other impairment like unilateral neglect after stroke. In recent years, constraint-induced therapy can also combine with telehealth and home rehabilitation. In addition, constraint-induced therapy produces significant neuroplastic changes in the central nervous system. Functional magnetic resonance imaging, diffusion tensor imaging, and other imaging/electrophysiology methods have been used to clarify the mechanism and neuroplasticity. However, constraint-induced therapy has some limitations. It can only be used under certain conditions, and the treatment time and effectiveness are controversial. Further research is needed to clarify the mechanism and effectiveness of CI therapy.